Modeling and Control of the Oxygen Concentration in a Post Combustion Chamber of a Gas-Fired Furnace*. Issue 1 (July 2017) - Strommer, Stephan; Froehlich, Christoph; Niederer, Martin; Steinboeck, Andreas; Kugi, Andreas
Abstract: Gas-fired industrial furnaces are used for heat-treatment of semi-finished steel products. The required energy is provided by gas-fired burners, which are supplied by fuel and air. The combustion is often realized fuel rich to avoid scale formation at the product surface. Thus, the flue gas contains unburnt products, which are oxidized in a post combustion chamber by adding fresh air. The control of the volume flow of air to the post combustion chamber is a crucial task because the flue gas leaving the furnace must not contain unburnt products. For this control task, a two-degrees-of-freedom control strategy based on differential flatness in combination with a MIMO-PI controller is proposed. The basis for the control design is a first-principles mathematical model of the air supply circuit and the combustion of flammable products. The model is validated by means of measurement data from a real plant.